Presença de gramíneas forrageiras exóticas em área de floresta ombrófila densa em Blumenau/SC: plantas forrageiras sob o enfoque de plantas invasoras - Klein, Sabrina Maria (2009)
Four forage grasses from botanic alien species - Tripsacum dactyloides, Axonopus scoparius, Panicum maximum and Melinis minutiflora - were found in a fragment of Forest Dense Ombrófila Submontana in process of recruitment, in an urban environment in Blumenau, Santa Catarina state, in the South of Brazil. The vegetation of this forest area was inventoried. The classification of the natural regeneration of secondary vegetation showed a predominance of medium sucessional stages. In initial sucessional stages, herbaceous plants were found among non-native forage grasses. The species Melinis minutiflora and Panicum maximum were found along the border of the fragment, close to highways, isolated and not forming large clumps. Both are recorded in the invasive alien species database managed by the Horus Institute for Environmental Conservation and Development (www.institutohorus.org.br), part of the I3N invasive alien species thematic network, a component of IABIN (Inter American Biodiversity Information Network). Tripsacum dactyloides and Axonopus scoparius don't appear in such a bank, which includes Brazil. Both species were assessed through the software developed by the I3N invasive alien species thematic network, the Risk Assessment Tool for the Establishment and Invasion by nonnative species. The data assessment on Tripsacum dactyloides shows that it poses a high risk for its potential in becoming an invasive species. There was no conclusive resulted about the species Axonopus scoparius due to the inadequacy of information available on the species.